Contribution to the flora of Málaga - Smythies, B. E. (Universidad de Málaga, Servicio de Publicaciones, 1976)
Se da una lista de plantas recolectadas o vistas por el autor en la provincia de Málaga o localidades limítrofes.

A list is given of plants collected or sighted by the author in Málaga province or nearby.